Fantastic Beasts: Unfolding Mixoplankton Temporal Variability in the Belgian Coastal Zone Through DNA-Metabarcoding - Lapeyra Martin, Jon; John, Uwe; Royer, Colin; Gypens, Nathalie (Frontiers in Marine Science, 2022)
Protists engaging in photo- and phago- mixotrophy (mixoplankton) are common members of the global plankton community. They are involved in primary production and contribute to the carbon and nutrient cycling. Two major mixoplankton functional types (MFTs) are considered based upon the origin of their photosynthetic abilities: innate for constitutive-mixoplankton (CM) and obtained from prey for non-constitutive mixoplankton (NCM). Regardless of their significance, little attention has been paid to their diversity and temporal succession. We performed a metabarcoding survey of the V4-18S rRNA gene in 92 surface water samples collected during 2018–2019 in five fixed stations of the Belgian Coastal Zone. Environmental data such as nutrients, sea surface temperature, salinity, Chl-a and light were collected to understand their influences over mixoplankton community changes. The temporal diversity of mixotrophs, autotrophs, and heterotrophs was analyzed and the distinct seasonal patterns were evidenced. Results showed that dinoflagellates and ciliates were the major mixoplankton contributors. There were no significant differences among protist communities between the stations sampled. The time-series showed high proportional abundances of CM, accounting in average for 24.4% of the reads, against the low contribution of NCM, 4.8%. CM dinoflagellates belonging to Heterocapsa, Alexandrium, Karlodinium, and Tripos genus were the most abundant, and co-occurred with strict autotrophic plankton. Strombidium genus ciliates were the most representative organisms for NCM. Mixoplankton showed lower diversity than autotrophs and heterotrophs throughout the time series, however, the environmental factors controlling the seasonal community shifts (β-diversity) were similar. Overall, the metabarcoding approach allowed to depict with high resolution the composition of mixoplankton and its diversity among auto- and heterotrophs in the Belgian Coastal Zone.